Empowering Cities : Good for Growth? Evidence from China - Zhu, T. Juni (World Bank Group, Washington, DC, 2015)
This paper utilizes a countrywide, county-to-city upgrade in the 1990s to identify whether extending the powers of urban local governments leads to better firm outcomes. The paper hypothesizes that since local leaders in newly-promoted cities have an incentive to utilize their new administrative remit to maximize gross domestic product and employment growth, there should be improvements in economic outcomes. The analysis finds that aggregate firm-level outcomes do not necessarily improve after county-to-city graduation. However, it does find that state-owned enterprises perform better post-graduation, with increased access to credit through state-owned banks as a possible explanation for the improvement in performance. The most important finding is that newly-promoted cities with high capacity generally produce better aggregate firm outcomes compared with newly-promoted cities with low capacity. The conclusions are twofold. First, in terms of access to credit, the paper provides evidence that relaxing credit constraints for firms could lead to large increases in firm operation and employment. Second, increasing local government's administrative remit is not enough to lead to better firm and economic outcomes; local capacity is of paramount importance.